2020
DOI: 10.2147/dmso.s272147
|View full text |Cite
|
Sign up to set email alerts
|

<p>Renoprotective Effect of Formononetin by Suppressing Smad3 Expression in Db/Db Mice</p>

Abstract: Purpose: Glomerular sclerosis and renal interstitial fibrosis are the most important pathologies in the development of kidney damage under diabetic conditions. Smad3 plays antagonistic roles in high glucose-induced renal tubular fibrosis, which is an important treatment target for diabetic nephropathy (DN). Formononetin (FMN) has multiple effects on diabetic vascular complications including DN. However, whether it plays an anti-fibrosis role by regulating smad3 is unclear. The purpose of this study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Firstly, we investigated the effects of FMN on renal function and morphological changes in diabetic rats. Several studies explored the renal protective effects of FMN in type 2 diabetes models ( Oza and Kulkarni, 2019 ; Lv et al, 2020 ; Zhuang et al, 2020 ). Our study aimed to investigate the protective effects of FMN on renal tubular impairment and mitochondrial dysfunction in STZ-induced type 1 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we investigated the effects of FMN on renal function and morphological changes in diabetic rats. Several studies explored the renal protective effects of FMN in type 2 diabetes models ( Oza and Kulkarni, 2019 ; Lv et al, 2020 ; Zhuang et al, 2020 ). Our study aimed to investigate the protective effects of FMN on renal tubular impairment and mitochondrial dysfunction in STZ-induced type 1 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that formononetin can improve glucose and lipid metabolism, reduce oxidative stress, and protect the kidney in diabetic db/db mice. Moreover, the inhibition of Smad3 protein and related regulatory factors of extracellular matrix could contribute to alleviation of renal fibrosis [ 27 ]. Kaempferol has anti-inflammation, antioxidation, antidiabetes, and antiaging effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is compatible with [20], which showed that AST and ALT levels were reduced after A. annua L treatment. A. annua L. was reported to improve proteinuria and eliminate NS progression [21]. Many researches have also argued that ARS can minimize renal lesion in rats by inhibiting the platelet-derived plant growth factor B expression (PDGF-B) [22], metalloproteinase tissue inhibitor-2 spatiotemporal activation of protein kinase c (PKC), and its hetero-demer function [23].…”
Section: Ns: Non Significantmentioning
confidence: 99%